Unveiling the additive-assisted oriented growth of perovskite crystallite for high performance light-emitting diodes - Lin Zhu (Nature Portfolio, 2021)
Additives have been widely used for passivating defects in perovskite semiconductors, yet the role of additive and their interaction is not clear. Here, the authors reveal an additive-assisted crystal formation in FAPbI3 perovskite by tracking the chemical interaction in the precursor solution and crystallographic evolution using multi-functional additives.